Preface - Nowak, Andrzej J. (Computer Assisted Methods in Engineering and Science, 2013)
Papers published in this special issue (and the papers of already published special issue CAMES  2/2013) have been presented during the Numerical  Heat  Transfer  2012  International  Conference (NHT2012).